Prevalence of oral soft-tissue lesions in out-patients at 2 Malaysian and Thai dental schools - Zain, R.B.; Siwamogstham, P.; Axell, T.; Thampipit, J.; Tantiniran, D. (Blackwell Publishing, 1990)
At the Faculties of Dentistry in Chiang Mai, Thailand (CM), and Kuala Lumpur, Malaysia (KL), 234 and 233 consecutive out-patients of mean ages 33.8 and 31.0 yr, respectively, were examined for the presence of oral mucosal lesions. Tobacco in some form was regularly used by 31.7% and 27.5% of the study populations in CM and KL, respectively. Cigarette smoking was the predominant habit. In CM three persons chewed betel quids and nine smoked banana leaf cigars daily. In addition, there were 24 habitual chewers of tea leaves (miang). In KL six persons chewed betel quids daily. In CM and KL three cases each (1.3%) of tobacco-associated leukoplakias were found. In KL an additional idiopathic leukoplakia was registered. One and three cases of betel related lesions were found in CM and KL, respectively. One case of a squamous cell carcinoma was found in a 45-yr-old Indian woman in KL who had been chewing betel with tobacco daily for many years. High prevalence figures were found for lichen planus, 3.8% in CM and 2.1% in KL, and an extremely high one, 48.3%, in CM for episodes of aphthous ulcers experienced during the last 2 yr. Comparatively low prevalence figures were found for herpes labialis. As could be expected melanin pigmentation was prevalent while only low figures were encountered for denture-related lesions and amalgam tattoos.